PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV PADA MATERI DIAGRAM BATANG SDN 178 GEGERKALONG KPAD - Ira Rosita; Sandi Budi Iriawan; Iman Indrayana (Jurnal Komunikasi, 2026)
Education in the modern era demands innovation in the learning process to prepare students to face the challenges of the 21st century. One of the innovations implemented is the Problem Based Learning (PBL) learning model, which encourages students to be active in problem solving. This research aims to determine the effectiveness of implementing PBL in improving learning outcomes for bar diagram material in class IV SDN 178 Gegerkalong KPAD. The research method used is Classroom Action Research (PTK) with the Kemmis and McTaggart model which consists of two cycles. Each cycle includes planning, implementation, observation, and reflection. The research results show a significant increase in student learning outcomes. In the first cycle, 85% of students achieved the Learning Goal Achievement Criteria (KKTP), while in the second cycle this increased to 96%. These results indicate that the PBL model is effective in improving students' understanding and learning outcomes in bar chart material. However, there is still one student who has not reached the KKTP, who requires further intervention from the teacher.